Why don’t we have an effective tuberculosis vaccine yet? - Davenne, T; McShane, H (Taylor and Francis, 2016)
Mycobacterium tuberculosis (M.tb) has co-evolved with humans for thousands of years, to cause tuberculosis (TB). The success of M.tb as a pathogen is in part because of the ways in which M.tb evades and exploits different cell subsets, to persist and cause disease. M.tb expresses numerous molecules to prevent its recognition and destruction by immune cells. The only licensed vaccine against TB, Bacillle Calmette-Guerin (BCG), is effective at preventing disseminated disease in infants but confers highly variable efficacy against pulmonary TB in adults, particularly in the developing world. A greater understanding of the reasons for this variability, together with a better understanding of the early, innate, and non-antigen specific mechanisms of protection would facilitate the design and development of more effective vaccines.